Research Progress of Extracellular Vesicles-Loaded Microneedle Technology - Xue Wang; Wei Cheng; Jiandong Su (Pharmaceutics, 2024)
Microneedles (MNs), renowned for their painless and minimally invasive qualities, exhibit significant potential for facilitating effective drug delivery, vaccination, and targeted sample extraction. Extracellular vesicles (EVs), serving as cargo for MNs, are naturally occurring nanovesicles secreted by cells and characterized by novel biomarkers, low immunogenicity, and cell-source-specific traits. MNs prove instrumental in extracting EVs from the sample fluid, thereby facilitating a promising diagnostic and prognostic tool. To harness the therapeutic potential of EVs in tissue repair, MNs with sustained delivery of EVs leverage micron-sized channels to enhance targeted site concentration, demonstrating efficacy in treating various diseases, such as Achillea tendinopathy, hair loss, spinal cord injury, and diabetic ulcers. EV-loaded MNs emerge as a promising platform for repair applications of skin, cardiac, tendon, hair, and spinal cord tissues. This review commences with an overview of MNs, subsequently delving into the role of EVs as cargo for MNs. The paper then synthesizes the latest advancements in the use of EV-loaded MNs for tissue regenerative repair, extending to research progress in extracting EVs from MNs for disease diagnosis and prognostic evaluations. It aims to offer valuable insights and forecast future research trajectories with the hope of inspiring innovative ideas among researchers in this field.